Alat Otomatis Pembuat Keripik Singkong Dengan Pengirisan Berdasarkan Tingkat Ketebalan dan Fungsi Pengeringan: Automatic Cassava Chips Maker with Thickness-Based Slicing and Drying Function - syafrudin, Muhammad Ilham (Jurnal Elektronika dan Otomasi Industri, 2025)
This research aims to develop an automatic cassava chips maker that can produce chips with a consistent thickness based on control settings and drying functions. The method used involves the design and implementation of an automation system consisting of a thickness sensor, a microprocessor controller, and a drying system. A thickness sensor is installed to monitor the thickness of the cassava being processed, while a microprocessor controller regulates the chip making process automatically based on data received from the sensor. The drying system was developed to ensure the final result has the desired level of crispness. Experimental results show that this automatic tool is capable of producing cassava chips with a consistent thickness, as well as providing good control over the drying process. With this tool, it is hoped that it can increase efficiency and consistency in mass production of cassava chips. This research contributes to the development of automation technology in the cassava- based snack industry.